Health care policy and reform a comparative study of policy making and the health care systems in five OECD countries. - Le Fevre, Anne M. (Curtin University, 1997)
Many of the assumptions underlying health care issues appear to be taken for granted by policy makers, when if fact they ought to be examined for their relevance to today's problems. This research attempts to do so, by analysing the non-economic issues and factors involved in the financing and provision of health care. It will be argued that policy makers commonly have a unidirectional economic perspective in both policy making and in health care system reform directives, a situation which leaves issues such as the health status of the population and of equity in resource allocation to political rhetoric, while in practice, policies deal with the issue of cost reduction. Of major importance is the moral dimension in policies dealing with health and welfare, which is clearly either forgotten or is afforded too little consideration in policy making. This is particularly relevant to the issue of rationing of health care in publicly provided health care systems. While always quietly practised by clinicians in the past, rationing is now required to be overt because demand for health care has outstripped available resources.The substance of the argument comes from the analysis of a very large literature on the broader issues affecting health care policy, such as concepts of social justice, ethics of resource allocation and the physician-patient relationship, all of winch ought to underpin policies for the mechanisms of funding and provision of health care systems.A conceptual diagram of a health care system is offered to provide a framework for the discussion of how the issues are interrelated at micro, meso and macro levels in policymaking. Examples of reforms to health care systems are taken from five OECD countries which share a common social, political and economic heritage: Australia, United Kingdom, New Zealand, Canada and the United States of America.The conclusions from this research show that theoretical incoherence pervades this most complex of policy areas, allowing the economic imperative to take precedence over the substantive health care issues.